Paediatric phantom dose study using digital radiography with variation of exposure parameters and filtration - Lança, Luís (2018)
Paediatric digital radiography remains a challenge for many radiographers. The subsequent need for focused paediatric care is outlined by ‘The Image Gently Campaign’, which reports a lack of both expertise and educational resources surrounding this area. This requirement is reinforced by The International Commission on Radiological Protection (ICRP), which identifies a need for both optimisation and consistency in digital paediatric imaging. Although a considerable proportion of recent research surrounds paediatric diagnostic imaging, Jones et. al highlights an absence of literature regarding optimisation in paediatric extremity imaging.This is of particular importance when considering paediatric patients who, due to their additional life expectancy and increased tissue radio-sensitivity, are considerably more sensitive to the detrimental effects of ionising radiation. Although the radiation dose received for diagnostic purposes is low, it is pertinent that each exposure be minimised due to the cumulative nature of radiation. The question to be addressed through our study is as follows; using a paediatric phantom with multiple bone fractures, could the variation of exposure parameters and filtration in digital radiography achieve a reduction in dose without substantially affecting image quality? This study aims to evaluate the variation of exposure parameters and filtration in image quality and dose in a paediatric phantom study using a digital radiography (DR) wireless detector.